Effects of physical exercise during pregnancy on delivery outcomes: Systematic review and meta-analysis of randomized controlled trials - Betelhem Abebe Andargie; Abdrehman Legas; Abebe W/Sellassie; Habtamu Abuhay; Dessie Abebaw Angaw (PLoS ONE, 2025)
Background Pregnant women should engage in a range of physical activities as it is not only safe but also has many maternal benefits. This systematic review and Meta -analysis aimed to assess the pooled effect of physical exercise during pregnancy on delivery outcomes. Method We conducted a systematic literature search on PubMed, Cochrane Library, Science Direct, Embase, Scopus, HINARI, PsycINFO, Google Scholar, and backward and forward citations for studies published since 2010. Only randomized controlled trials (RCTs) published in English, assessing the effect of exercise on the mode of delivery as a primary or secondary outcome, were included. Quality assessment was performed using Cochrane guidelines, and the certainty of evidence was evaluated using the GRADE approach. A random-effects model was used for meta-analysis, and results were reported as risk ratio (RR) and weighted mean difference (WMD) with 95% confidence intervals (CIs). Heterogeneity was assessed using I² statistics, and potential publication bias was examined. The primary outcome was the mode of delivery, while secondary outcomes included duration of labor, Apgar score, and birth weight. Results A total of 16 RCTs involving 3,387 women (1,704 exercise and 1,683 control)were included. Compared to the control group, pregnant women with exercise interventions had a higher rate of normal vaginal delivery (RR = 1.14, 95% CI: 1.08–1.21, I² = 25.6%, moderate certainty of evidence) and a significantly lower rate of cesarean delivery (RR = 0.66, 95% CI: 0.55–0.80, I² = 22.47%, high certainty of evidence). However, no statistically significant association was found between exercise and instrumental delivery (RR = 0.84, 95% CI: 0.70–1.02, moderate certainty of evidence). The mean duration of the first stage of labor was significantly shorter in the exercise group (WMD = −61.30 minutes, 95% CI: −80.63 to −41.97, moderate certainty of evidence). However, no significant differences were observed for second stage of labor birth weight, Apgar scores at one and five minutes (moderate certainty of evidence). Conclusion This systematic review and meta-analysis consolidate existing evidence, demonstrating that physical exercise is associated with an increased likelihood of normal vaginal delivery, a reduced rate of cesarean delivery, and a shorter first stage of labor. These findings reinforce the importance of encouraging pregnant women without contraindications to engage in appropriate physical activity during pregnancy, contributing to informing clinical practice. Trial registration This study was registered on PROSPERO number CRD42022361132.